2010
DOI: 10.1371/journal.pone.0012568
|View full text |Cite
|
Sign up to set email alerts
|

Being Attractive Brings Advantages: The Case of Parrot Species in Captivity

Abstract: BackgroundParrots are one of the most frequently kept and bred bird orders in captivity. This increases poaching and thus the potential importance of captive populations for rescue programmes managed by zoos and related institutions. Both captive breeding and poaching are selective and may be influenced by the attractiveness of particular species to humans. In this paper, we tested the hypothesis that the size of zoo populations is not only determined by conservation needs, but also by the perceived beauty of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 36 publications
10
94
1
7
Order By: Relevance
“…In case of boid snakes, human preferences are a good predictor of conservation efforts devoted to captive breeding of particular species in zoos worldwide, unlike its conservation status or present range size (Marešová and Frynta 2008). Similar evidence has been brought in case of parrot species (Frynta et al 2010) and other vertebrate taxa (Frynta et al 2009). If we assume that we inherently share an idea of what is beautiful and desirable in an animal, it is easy to imagine selective support or neglect of endangered species.…”
Section: Discussionmentioning
confidence: 75%
“…In case of boid snakes, human preferences are a good predictor of conservation efforts devoted to captive breeding of particular species in zoos worldwide, unlike its conservation status or present range size (Marešová and Frynta 2008). Similar evidence has been brought in case of parrot species (Frynta et al 2010) and other vertebrate taxa (Frynta et al 2009). If we assume that we inherently share an idea of what is beautiful and desirable in an animal, it is easy to imagine selective support or neglect of endangered species.…”
Section: Discussionmentioning
confidence: 75%
“…Previously, using a comparable design, we demonstrated that blue and yellow also significantly increases human preferences for parrot species (Frynta et al 2010). Psychologists have devoted much effort to analyze the influence of colors on human emotions and behavior (for reviews, see Ball 1965;Bellizzi, Crowley and Hasty 1983).…”
Section: Discussionmentioning
confidence: 99%
“…To score the attractiveness of each bird species, we adopted the already established method we used in our previous study (Frynta et al 2010). This assessment strategy of scoring pictures on the Internet uses only a limited scoring scale (see below), but it benefits from the ability to present pictures to the respondent consecutively and in large numbers.…”
Section: Testing Attractivenessmentioning
confidence: 99%
“…Several studies have already stressed the biased composition of zoo collections towards popular species, such as some large python species among the boids (Marešova and Frynta 2007) and colourful parrots (Frynta et al 2010). It is predictable that as fewer species are maintained in ex situ institutions-a trend due to both economic and animal welfare reasons-competition for zoo space will become more severe, with threatened but non-charismatic species destined to lose (Lernould et al 2003;Backer 2007).…”
Section: European Zoos and Global Biodiversitymentioning
confidence: 99%